Dietary fat without body weight gain increases in vivo MCF‐7 human breast cancer cell growth and decreases natural killer cell cytotoxicity. Issue 1 (4th September 2013) - Lamas, Bruno; Nachat‐Kappes, Rachida; Goncalves‐Mendes, Nicolas; Mishellany, Florence; Rossary, Adrien; Vasson, Marie‐Paule; Farges, Marie‐Chantal
Abstract: High‐calorie (HC) diet contributes to the increased incidence of obesity, which is a risk factor for breast cancer in postmenopausal women, and in particular for estrogen receptor (ER) positive tumors. This study investigated whether an HC diet increases human ER‐positive breast cancer progression and modulates natural killer (NK) cell functions. Four‐week‐old female BALB/c athymic nude mice were fed a HC diet (5320 kcal/kg) or standard calorie diet (SC, 2820 kcal/kg) for 6 mo. After 5 mo, the mice were randomly implanted with MCF‐7 breast cancer cells (SCT and HCT) or received an isovolumic injection (SC and HC) in both inguinal fat pads. Tumor growth was greater in the HCT group than in the SC group without change in body weight. The HC diet decreased the tumor expression of genes involved in the citrate cycle and in adiponectin and lipid metabolism but increased that of genes controlling glycolysis and angiogenesis. The tumor expression level of Ki67 was increased while that of the cleaved caspase 3 and the ER‐β and progesterone receptors was reduced. Tumor development in response to the HC diet was associated with smaller numbers and lower cytotoxicity of splenic NK cells. These results indicate that an HC diet without body weight gain increases ER‐positive breast cancer cell proliferation and reduces tumor apoptosis. The underlying mechanisms might involve a downexpression of tumor hormonal receptor and reduced NK cell functions, and might also result in the regulation of genes involved in several cellular functions. © 2013 Wiley Periodicals, Inc.